Advancing Personalised and Precision Medicine Through Artificial Intelligence: Current Insights and Future Directions - Fatima, Ghizal; Buttar, Harpal; Parvez, Sidrah; Khan, Sadaf; Mahdi, Abbas Ali; Raza, Ammar Mehdi (Scripta Medica, 2025)
The convergence of artificial intelligence (AI) and precision medicine is transforming healthcare by introducing a patient-centered, data-driven approach to treatment. Precision medicine, which tailors medical care based on individual characteristics, addresses the complexity and heterogeneity of diseases. The integration of AI into this field has unlocked unprecedented potential for enhancing disease management and advancing personalized care. AI leverages extensive datasets, including genomic sequences, clinical records, and molecular profiles, to identify patterns and predict outcomes with remarkable accuracy. Its capabilities extend beyond automation, functioning as a critical tool for informed clinical decision-making. By analyzing complex molecular data, AI enhances diagnostic precision through the detection of subtle biomarkers and anomalies frequently overlooked by traditional methods. Machine learning–powered predictive analytics further empower clinicians by forecasting disease progression and guiding treatment personalization. Practical applications of AI-driven precision medicine are already evident in clinical settings. From diagnosing rare genetic disorders to optimizing drug therapies based on genetic profiles, AI is fundamentally reshaping patient care. However, critical challenges, including ethical considerations, data privacy, and the need for transparent algorithms, persist. This review examines the synergistic relationship between AI and precision medicine, highlighting ongoing research, technological innovations, and interdisciplinary collaboration. Together, these advancements herald a transformative era in healthcare, paving the way for highly personalized and effective therapeutic strategies.